До історії філософії клубної культури Галичини (кінець ХІХ – початок ХХ ст.) - Ясінський, Михайло; Yasinskyy, Mychaylo (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано філософські позиції відомих політиків, діячів науки, культури та мистецтва краю, обґрунтовано основні філософські концепції клубної культури Галичини наприкінці ХІХ – на початку ХХ ст. The article focuses on the philosophical content of the club culture in the context of the concepts of ethnicity. Presented philosophical position known Ukrainian politicians, science, culture and the arts, who contributed to the development of philosophical and social thought in Galychyna late XIX − early XX century. Defined the main content of philosophical thought in Ukrainian Galychyna this period, contributing to the unification of the Ukrainian ethnos Galychyna, they develop self-awareness of its importance and uniqueness. Highlighted the features of the development of philosophical thought in Ukrainian Galychyna said period, analyzed the features of the Galychyna kulturphylosophy school. Clarified the content of the concept of ethnicity and cultural clubs. It is shown that the base of ethnicity and cultural clubs in Galychyna at the turn of the nineteenth and twentieth centuries laid out in historico-philosophical works, religious and ethnic ideas, ideas of social and political movements, and their very activity was associated with the development of the Ukrainian nation and Ukrainian state building .
To the History of Club Culture Philosophy of Galychyna at the End of XIX − the Beginning of XX Century
Keywords: історія розвитку філософських концепцій етнічно-клубної культури; history of philosophical concepts of ethnic club culture; філософія клубної культури Галичини; philosophy club culture of Galicia; історіософія культури; historical philosophy of culture